Apakah Faktor-Faktor dalam Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) Mempengaruhi Penggunaan Aplikasi Pesan-Antar Makanan pada UMKM Coffee Shop? - Fitri Yutika (Jurnal Manajemen dan Organisasi, 2023)
Coffee Shop is one of Food and Beverage (F&B) business that has a more functional purpose than culinary businesses in general. Coffee Shop does not only sell coffee drinks or its accompaniments, but a place that provides space and comfort for its customers while enjoying coffee and its accompaniments. This is a consideration for MSMEs whether Coffee Shops will be more effective if they adopt online food delivery services. This study aims to explore the factors that influence the adoption of Food Delivery Applications (FDA) in MSMEs Coffee Shop based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). The research was conducted on 70 MSMEs Coffee Shop in Pontianak City by distributing questionnaires. Data were analyzed using the Structural Equation Modeling method with SmartPLS software. The results showed that the personal innovativeness variable had a significant positive effect on FDA's adoption behavior at the coffee shop MSMEs in Pontianak City. Coffee shop entrepreneurs in Pontianak City do not consider performance expectancy, supporting infrastructure, community and consumer needs, technological security levels, or the cost of using food delivery services. While previous studies hAVE identified factors influencing people's technology adoption behavior with the UTAUT2 theory, this study showed that the factors that shape coffee shop behavior are different from F&B businesses generally in terms of adopting food delivery. Factors outside the UTAUT2 theory need to be analyzed in future studies to explore factors influencing FDA adoption by coffee shop MSMEs.